Test of the Binding Threshold Hypothesis for olfactory receptors: Explanation of the differential binding of ketones to the mouse and human orthologs of olfactory receptor 912-93 - Hummel, Patrick (Cold Spring Harbor Laboratory Press, 2005)
We tested the Binding Threshold Hypothesis (BTH) for activation of olfactory receptors (ORs): To activate an OR, the odorant must bind to the OR with binding energy above some threshold value. The olfactory receptor (OR) 912-93 is known experimentally to be activated by ketones in mouse, but is inactive to ketones in human, despite an amino acid sequence identity of ∼66%. To investigate the origins of this difference, we used the MembStruk first-principles method to predict the tertiary structure of the mouse OR 912-93 (mOR912-93), and the HierDock first-principles method to predict the binding site for ketones to this receptor. We found that the strong binding of ketones to mOR912-93 is dominated by a hydrogen bond of the ketone carbonyl group to Ser105. All ketones predicted to have a binding energy stronger than E(BindThresh) = 26 kcal/mol were observed experimentally to activate this OR, while the two ketones predicted to bind more weakly do not. In addition, we predict that 2-undecanone and 2-dodecanone both bind sufficiently strongly to activate mOR912-93. A similar binding site for ketones was predicted in hOR912-93, but the binding is much weaker because the human ortholog has a Gly at the position of Ser105. We predict that mutating this Gly to Ser in human should lead to activation of hOR912-93 by these ketones. Experimental substantiations of the above predictions would provide further tests of the validity of the BTH, our predicted 3D structures, and our predicted binding sites for these ORs.